Monitoring of Foot Oxygenation with Near-infrared Spectroscopy in Patients with Critical Limb Ischemia Undergoing Percutaneous Transluminal Angioplasty: A Pilot Study. Issue 5 (November 2016) - Boezeman, R.P.E.; Becx, B.P.; van den Heuvel, D.A.F.; Ünlü, Ç.; Vos, J.A.; de Vries, J.P.P.M.
Abstract : Objective: Near-infrared spectroscopy (NIRS) non-invasively determines tissue oxygen saturation (Sto 2 ) in muscle tissue. Its application to monitor real time hemodynamic changes during percutaneous transluminal angioplasty (PTA) and Sto 2 changes in feet 4 weeks after PTA was evaluated. Methods: This study included 14 patients with critical limb ischemia (CLI, six patients Rutherford classification Stage IV, two patients Stage V, and six patients Stage VI). In patients with arterial ulcers, NIRS optodes were placed near the ulcer of the diseased foot (Optode 1), and at the same spot at the contralateral foot (Optode 2). In patients without arterial ulcers, Optode 1 was placed on the dorsum of the diseased foot, and Optode 2 was placed on the dorsum of the contralateral foot. Single Sto 2 values, ankle brachial indices, and toe brachial indices were obtained at rest before the start of endovascular revascularization and 4 weeks after treatment. During the endovascular procedure, continuous Sto 2 measurements were recorded throughout the intervention. Completion angiograms were used to evaluate the success of intervention. Results: Patients underwent treatment of the superficial femoral artery (79%), popliteal artery (21%), and below the knee arteries (43%). In 13 of the 14 patients, completion angiograms showed successful treatment of target lesions. Ankle brachial indices and toe brachial indices significantly increased 4 weeks after treatment (both p  < .01). Single Sto 2 values of Optode 1 also significantly increased four weeks after treatment ( p  < .01). In contrast, single Sto 2 values of Optode 2 did not ( p  = .73). During the endovascular procedure, continuous Sto 2 measurements of Optode 1 and 2 did not increase ( p  = .80, and p  = .61, respectively). Conclusions: NIRS monitoring of foot oxygenation in patients undergoing endovascular revascularization is safe and feasible. NIRS is a promising non-invasive technique to monitor hemodynamic changes in the feet of CLI patients after endovascular treatment using single Sto 2 values.